1985
DOI: 10.1017/s0033291700023606
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and platelet monoamine oxidase in tobacco smokers

Abstract: SynopsisA study was made of the smoking habits of an unselected series of 1129 18-year-old men from the general population. Their smoking habits were related to personality traits, intellectual level and platelet monoamine oxidase (MAO). Regular smokers were found to be extraverts, sensation seekers who were easily bored and with a strong tendency to avoid monotony. They also had a lower than average intellectual level, and were more prone to the abuse of alcohol, glue, cannabis, amphetamine and morphine. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(14 citation statements)
references
References 20 publications
1
12
0
1
Order By: Relevance
“…Both MAO-A and MAO-B levels have been implicated to play a role in smoking cessation (Fowler, Logan, Wang, & Volkow, 2003) and a number of early studies have reported that smokers have reduced MAO levels as compared to nonsmokers (Fowler et al, 1996;Oreland, Fowler & Schalling, 1981;Norman, Chamberlain, & French, 1987;Norman, Chamberlain, French, & Burrows, 1982; Von Knorring & Oreland, 1985). Initially, low levels of MAO were considered to be a predisposing factor for the development of neurological diseases such as MDD and schizophrenia (Buchsbaum, Coursey, & Murphy, 1976;Wyatt et al, 1980).…”
Section: Smokingmentioning
confidence: 99%
“…Both MAO-A and MAO-B levels have been implicated to play a role in smoking cessation (Fowler, Logan, Wang, & Volkow, 2003) and a number of early studies have reported that smokers have reduced MAO levels as compared to nonsmokers (Fowler et al, 1996;Oreland, Fowler & Schalling, 1981;Norman, Chamberlain, & French, 1987;Norman, Chamberlain, French, & Burrows, 1982; Von Knorring & Oreland, 1985). Initially, low levels of MAO were considered to be a predisposing factor for the development of neurological diseases such as MDD and schizophrenia (Buchsbaum, Coursey, & Murphy, 1976;Wyatt et al, 1980).…”
Section: Smokingmentioning
confidence: 99%
“…Some, but not all these findings could be related to the direct effect of smoking on the enzyme activity. It has been suggested that low platelet MAO itself predicts smoking [35,36], and indeed, in a longitudinal study, it has been demonstrated that not only does smoking inhibit platelet MAO activity, but platelet MAO activity contributes to becoming a regular smoker [37]. However, in the latter study as well as in the investigation of Alm et al [38], which reported that among juvenile delinquents, both low and high platelet MAO activity subjects were over-represented, the factor contributory to deviant behavior was the deviation from the population mean enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…MAO-A and MAO-B are both involved in the degradation of catecholamines and serotonin. The activity of MAOs is decreased in smokers (Norman et al 1987;Von Knorring and Oreland, 1985), and MAO activity returns to normal after cessation of smoking (Fowler et al 1996;Whitfield et al 2000). Decreases in MAO activity in smokers may be related to the inhibitory effects of harmanes contained in tobacco.…”
Section: Discussionmentioning
confidence: 99%